2020
DOI: 10.1111/jcpp.13198
|View full text |Cite
|
Sign up to set email alerts
|

Early pubertal timing predicts onset and recurrence of depressive episodes in boys and girls

Abstract: Background: Recurrent depressive episodes during adolescence result in significant impairment and increased risk for subsequent adverse outcomes throughout the life span. Evidence suggests that early pubertal timing predicts the onset of depressive episodes (particularly for girls); however, it is not known if pubertal timing prospectively predicts recurrent depressive episodes in youth. Methods: At baseline, 603 youth (56% female, at baseline: M age = 12.09, SD = 2.35) reported on their pubertal development. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 59 publications
1
25
0
Order By: Relevance
“…Moreover, including the equivalent Time 1 psychopathology measure did not eliminate or weaken the results. Few previous studies have controlled for the history of psychopathology when examining how early timing is related to internalizing psychopathology, and the two studies that did this showed conflicting findings (Crockett et al, 2013; Hamlat et al, 2020). Our specification curve analysis included a decision point of whether or not to control for Time 1 psychopathology and thus showed that associations between pubertal timing and internalizing psychopathology remained after controlling for this variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, including the equivalent Time 1 psychopathology measure did not eliminate or weaken the results. Few previous studies have controlled for the history of psychopathology when examining how early timing is related to internalizing psychopathology, and the two studies that did this showed conflicting findings (Crockett et al, 2013; Hamlat et al, 2020). Our specification curve analysis included a decision point of whether or not to control for Time 1 psychopathology and thus showed that associations between pubertal timing and internalizing psychopathology remained after controlling for this variable.…”
Section: Discussionmentioning
confidence: 99%
“…Of the handful of prospective longitudinal studies available, some show that various measures of pubertal timing (Conley et al, 2012; Copeland et al, 2010; Graber et al, 2004; Marceau et al, 2011) have been prospectively associated with internalizing psychopathology in later adolescence and sometimes through young adulthood, although not always (Lee et al, 2017). There is also conflicting evidence whether early timing is related to internalizing psychopathology when controlling for history of psychopathology (Crockett et al, 2013; Hamlat et al, 2020). This has implications for identifying the best time window for prevention and early intervention efforts that mitigate the risk of internalizing psychopathology.…”
mentioning
confidence: 99%
“…Few previous studies have controlled for history of psychopathology when examining how early timing is related to internalizing psychopathology, and the two studies that did this showed conflicting findings. 28,29 Our study explicitly tested the same associations with and without Time 1 psychopathology as a control variable and thus showed that associations between pubertal timing and internalizing psychopathology remained after controlling for this variable. Although our methods do not allow us to infer causality, these findings provide an indication that the likely direction of effect is from pubertal timing to internalizing psychopathology.…”
Section: Measure Of Internalizing Psychopathologymentioning
confidence: 93%
“…27 There is also conflicting evidence whether early timing is related to internalizing psychopathology when controlling for history of psychopathology. 28,29 This has implications for identifying pubertal timing as a potential risk factor for the onset of mental health problems during adolescence, which could inform prevention and early intervention efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Pubertal development also interacts with psychosocial factors that may influence the development of internalizing symptoms. Much of the extant literature focuses on pubertal timing and suggests that adolescents with early pubertal timing are more likely to develop internalizing symptoms throughout adolescence [28] and adulthood [29], particularly females [30]. Furthermore, pubertal timing is associated with internalizing symptoms—both cross-sectionally and prospectively—when pubertal development is measured by physical assessments, but not by sex hormone levels [31].…”
Section: Introductionmentioning
confidence: 99%